Titu Mir - Devi, Mahasweta; Chatterjee, Rimi K. (Calcutta : Seagull Books, 2000)
Novel, based on Titto Meer, 1782-1831, peasant leader who led a revolt against the British in Bengal.
GenEd
Development Book Agency, Hye Trade International
Keywords: Titto Meer, -- 1782-1831 -- Fiction; Bengali literature